PENGEMBANGAN MEDIA “KLIK AJA” DALAM PEMBELAJARAN DARING MENYAMPAIKAN TEKS BERITA BAGI SISWA KELAS VIII (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
The Covid-19 pandemic is a new challenge in the world of education, especially for a teacher, because learning must be done online. Therefore, teachers must master digital skills and creative thinking patterns, especially in conveying news texts. Facing this, this study discusses the development of online-based interactive learning media. The media development was designed by utilizing the Articulate Storyline 3 software in collaboration with learning videos and Google forms which were then combined on the Linktree website. The objectives of this study include describing the development of media and the presentation/display of the